ICTE 2011 [electronic resource] : proceedings of the third international conference on transportation engineering July 23-25, 2011 Chendu, China - International Conference on Transportation Engineering (3rd : 2011: Chendu, China); Peng, Qiyuan, editor; Wang, Kelvin C.P., editor; Qiu, Yanjun, editor; Pu, Yun, editor; Shuai, Bin, editor (Reston, VA : American Society of Civil Engineers, 2011)
PSZJBL